CSR SEBAGAI DAKWAH BIL HAL : Studi Kasus Implementasi CSR pada PT. Semen Tonasa - Nurul Islam; Thoha Mun'im Masykur (Rumah Jurnal STAIN Majene, 2022)
Da'wah is not always through the pulpit to call for good but can be done through social-environmental practices. PT. Semen Tonasa carries out community development and environmental development as a means to spread goodness. This study was conducted using qualitative research methods and descriptive research types. PT. Semen Tonasa (shareholders) and interested stakeholders as research subjects and objects, namely implementing corporate social responsibility through community development at PT. Semen Tonasa (Persero). CSR through the Triple Bottom Line Theory, namely Profit, People and Planet. So corporate social responsibility is part of the company's activities carried out continuously in the long term with the impact shown by the company's operations. The concept is the application of the type of direct involvement of social institutions or organizations fostered by the company and in partnership with other parties. The da'wah bil-hal approach carried out by PT Semen Tonasa is solely to call on humanity to be able to avoid Surat Arrum verse 41.